Social partnership as a mode of governance: introduction to the special issue - O Riain, Sean (Economic & Social Studies, 2006)
The development of ?social partnership? institutions has been one of the most striking, and surprising aspects of the transformation of Irish society and politics in the past fifteen years. The papers in this special issue explore the character of social partnership as a distinctive mode of governance ? examining partnership in action at national and local levels and in interaction with the EU, in macroeconomic bargaining, in sectoral and environmental policy, and in urban and rural settings. The papers are all extensive revisions of papers first presented at a conference on ?Social Partnership: A New Mode of Governance?? at the National University of Ireland, Maynooth in September 2004. The conference was generously funded by the Irish Research Council for The Humanities and Social Sciences and was held under the auspices of the National Institute for Regional and Spatial Analysis and the Department of Sociology at NUI Maynooth.
First presented at a conference on ?Social Partnership: A New Mode of Governance?? at the National University of Ireland, Maynooth in September 2004
Keywords: Social partnership; Governance; Ireland; Policy